The approach and mission of the auditor in Algeria - KATEB , Karim (Journal of Research in Finance and Accounting, 2023)
The objective of this article is to see the role and the mission of the auditor in Algeria, as well as the approach used for the conduct of his mission. We will see in this research article the standard work file made available to the auditor while relying on the standard reference of December 04, 2019 of the National Accounting Council, Quality Control Commission of the standard work file, relating to its implementation and which constitutes a reference document for the statutory audit mission.